THE EFFECT OF PUZZLE GAME THERAPY ON FINE MOTOR DEVELOPMENT IN CHILDREN 3-5 YEARS IN PLAY GROUP AISYIYAH 27 SURABAYA - Sholikhah, Dwi Uswatun; Puspita, Enny; Mardiah, Ainiyatul (Jurnal Keperawatan Universitas Jambi, 2024)
Delays in the development of fine motor skills in early childhood make children less confident and creative, this occurs due to a lack of effort due to excessive parental protection. Pre-school children are called the golden age, it is important to provide the right stimulation in order to support the development of children's fine motor skills which include hand muscles and can focus the child's vision in an optimal way. This study aims to determine the effect of puzzle gamesoon the fineamotor development ofuchildren aged 3-5 years at KB Aisyiyah 27 Surabaya. This study uses a quantitative method with a pre-experimental approach. The research population consisted of 52 children in groups A and B, and the research sample amounted to 30 respondents using the purposive sampling technique. Variables of fine motor development in children aged 3-5 years observed with the DDST II instrument. The results of the study showed that almost all respondents experienced fine motor delays (delayed) before being given puzzle game therapy as many as 23 respondents (77%). After being given puzzle game therapy, almost all respondents experienced an increase in fineamotor developmentawith a norm7al category of 28 (93%) while the caution category was 2 respondents (7%). From the results of the Wilcoxon test , the value of p = 0.000 (p < α = 0.05) was obtained, then H1 was accepted. This means that there is an influence of puzzle games on the fine motor development of children aged 3-5 years at the Aisyiyah 27 Surabaya KB (Play Group). Theaanalysis ofathis istudy uses the Wilcoxon test from SPSS VERSION 26 software. Puzzle games include correctly fixing images according to their shape, color and size to stimulate fine motor development in developing intelligence and problem-solving skills. In addition to puzzle games, parents can also stimulate playdough and coloring games